Characteristics of Qualitative Traits Color Patterns for Pure Bali Cattle and Brahman-Bali Cross - Junaedi Junaedi; Khaeruddin Khaeruddin; Muhammad Amin; Rosidi Azis; Aulia Firmawati; La Ode Muhammad Aswad Salam (Program Studi Peternakan Fakultas Sains dan Teknologi Universitas Muhammadiyah Sinjai, 2026)
The study was to examine the pattern of color distribution in pure cattle and cows from crosses between Brahman males and Bali breeds as a marker that can be an important criterion in livestock selection programs. This study used 50 pure Bali cattle and 50 crossbreed cows (Brahman-Bali Cross). The parameters observed were the cow's color pattern on the morphology of the head (face, eye iris, edge of the upper lip, muzzle, ear rims, inner ear, and horn), color pattern of body (backline, middle, lower abdomen, butt and tail end), and color pattern of leg and tight (nail, inner tight and leg). Data were analyzed descriptively, frequency, and displayed in percentage form. The characteristic color pattern of pure Bali cattle of 40% brick red face, 26% pale brown and 34% are black, the crossbreeding white 48%, brick red 22% and brownish red 30%. Pure Bali cattle have 100% black color on the iris, ear edge, muzzle, ear edge, and horns, the crossbreeding 74% black irises and 26% reddish irises. The foot morphology of the hoofs of pure cattle and crossbreeds was 100% black, while the inner thighs of both types were 100% white. The legs of pure cattle are brownish white 46% and white 54%, while the crossbreeds have 68% white and 32% reddish white. Body, head, and leg color patterns show clear genetic variation between purebred Bali cattle and their crossbred counterparts. These differences in color percentage can serve as practical visual markers for livestock selection and management.